The Sensory Processing 3-Dimensions Scale: Initial Studies of Reliability and Item Analyses - Shelley Mulligan; Sarah A. Schoen; Lucy Jane Miller; Andrea Valdez; Deborah Magalhaes (Scholarworks @ WMU, 2019)
Background: The Sensory Processing 3-Dimensions Scale (SP 3D) is a performance-based measure for assessing sensory processing abilities and challenges, including sensory modulation, sensory discrimination, and sensory-based motor disorders. Initial studies of reliability were conducted, and item response theory was applied to assist in refining the measure. Methods: Descriptive and correlational methods were used to examine internal consistency of the scales and inter-rater reliability. Item response theory using Rasch analyses was applied to examine unidimensionality of scales, model fit, and item difficulty. Results: Internal consistency for most measures was acceptable, demonstrating the subtests, domains, and behavior scales as distinct constructs. Inter-rater reliability results were mixed, with fair to strong reliability coefficients for most sensory discrimination and postural and praxis subtests. Scales measuring sensory modulation and motor behaviors had moderate to poor inter observer agreement. Rasch analyses supported subtests as unidimensional and identified the most rigorous items in the subtests. Conclusions: Preliminary results show promise of the SP-3D as a stable, reliable tool. A need for refinement of some operational definitions for behavior ratings was identified, and items to consider for elimination because of redundancy or ill-fit were exposed. Directions for research include refinement of the SP-3D and the need for further reliability and validity studies.